(untitled) (Vietnam Journal of Community Medicine, 2024)
Objectives: To determine the prevalence of online game addiction and its related factors among high school students in Can Gio District, Ho Chi Minh City, in 2024. Methods: A analytical cross-sectional study was conducted on 685 students from Binh Khanh High School and An Nghia High School in Can Gio District, Ho Chi Minh City. Students who agreed to participate were surveyed using a self-administered questionnaire about their personal, family, and school characteristics. Online game addiction was assessed using the Vietnamese version of the Internet Gaming Disorder scale (VN-IGD-17). Results: The prevalence of online game addiction among students was 13.7%. Male students were at higher risk than their female counterparts. Besides, students experiencing academic pressure were 16 times more likely to be addicted to online games than those without such pressure. Students playing MMOFPS and MOBA game genres had addiction risks 31 times and 26 times higher, respectively, compared to those playing MMORPG. Spending more than 30 hours per week on online games increased the addiction risk by 27 times compared to those spending less than 30 hours per week. Conclusion: The prevalence of online game addiction among students was 13.7%. Factors related are gender, conduct grades, academic pressure, game genres, and weekly gaming time.